Oral non-viral gene delivery for applications in DNA vaccination and gene therapy. (September 2018) - Farris, Eric; Heck, Kari; Lampe, Anna T.; Brown, Deborah M.; Ramer-Tait, Amanda E.; Pannier, Angela K.
Abstract: Non-viral gene delivery via the oral route is a promising strategy for improving outcomes of DNA vaccination and gene therapy applications. Unlike traditional parenteral administration routes, the oral route is a non-invasive approach that lends itself to high patient compliance and ease of dosing. Moreover, oral administration allows for both local and systemic production of therapeutic genes or, in the case of DNA vaccination, mucosal and systemic immunity. However, the oral route presents distinct challenges and barriers to achieving successful gene delivery. Oral non-viral gene delivery systems must be able to survive the harsh and variable environments (e.g. acidic pH, degrading enzymes, mucus layer) encountered during transit through the gastrointestinal tract, while still allowing for efficient transgene production at sites of interest. These barriers present unique design challenges for researchers in material selection and in improving the transfection efficiency of orally delivered genes. This review provides an overview of advancements in the design of oral non-viral gene delivery systems, and highlights recent and important developments towards improving orally delivered genes for applications in gene therapy and DNA vaccination. Graphical abstract: Highlights: Oral non-viral gene delivery is a promising strategy to prevent and treat diseases. Harsh GI conditions must be overcome for successful oral gene delivery. DNA vaccines and gene therapies can benefit from oral delivery. Dual material systems that protect DNA in the stomach are promising. Live-attenuated bacterial vectors represent a new approach to oral DNA vaccination.